2014
DOI: 10.1007/s00220-014-1982-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypercontractivity for Semigroups of Unital Qubit Channels

Abstract: Hypercontractivity is proved for products of qubit channels that belong to self-adjoint semigroups. The hypercontractive bound gives necessary and sufficient conditions for a product of the form e −t 1 H 1 ⊗ · · · ⊗ e −tnHn to be a contraction from L p to L q , where L p is the algebra of 2 n -dimensional matrices equipped with the normalized Schatten norm, and each generator H j is a self-adjoint positive semidefinite operator on the algebra of 2-dimensional matrices. As a particular case the result establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Actually, similar results have been already studied for semigroups consisting of tensor products of q-bits channels, i.e. of the form e −t 1 Hn ⊗ · · · ⊗ e −tnHn acting on M 2 n , where the tensor product structure was crucially exploited by the authors, see for instance [21,24].…”
Section: Introductionmentioning
confidence: 59%
“…Actually, similar results have been already studied for semigroups consisting of tensor products of q-bits channels, i.e. of the form e −t 1 Hn ⊗ · · · ⊗ e −tnHn acting on M 2 n , where the tensor product structure was crucially exploited by the authors, see for instance [21,24].…”
Section: Introductionmentioning
confidence: 59%
“…Theorems 1 and 2 will be proved in the next section. Our next two results present some special cases where there is no gap between potential purity and purity, that is where equality holds in (12). In the paper [13] it was shown that equality in (12) holds at q = 2 for a class of entanglement-breaking maps which includes the CQ maps.…”
Section: Resultsmentioning
confidence: 88%
“…Since this holds for all Ω we immediately get Φ (pot) q→p ≤ Φ q→p . The reverse inequality (12) follows immediately from the definition, so we deduce that equality holds.…”
Section: Proof Of Theoremmentioning
confidence: 75%
See 1 more Smart Citation
“…The bijection maps that preserve the quantum χ 2 κα divergence (see Example 3 about the family κ α ) have been characterized in [4], which complements the study of the contraction of quantum states. There are other tools based on the functional perspective, including quantum (reverse) hypercontractivity and related quantum functional inequalities [3,7,10,11,19].…”
Section: Related Techniques To Quantify the Loss Of Informationmentioning
confidence: 99%